Ongoing Response in a Multiply Relapsed Metastatic Posterior Fossa Ependymoma A After Vorinostat and Concomitant Irradiation. Issue 2 (March 2022) - Gorsi, Hamza S.; Toll, Stephanie A.; Sood, Sandeep; Miler, Steven; Altinok, Deniz; Kumar-Sinha, Chandan; Mody, Rajen; Yankelevich, Maxim
Abstract : Posterior fossa ependymomas A confer the worst prognosis among all subtypes. They demonstrate distinct epigenetic changes, which can be targeted with epigenetic modifiers like histone deacetylase inhibitors (Vorinostat). We describe a 3-year-old male diagnosed with a posterior fossa ependymoma who had a number of recurrences requiring multimodal therapy. Molecular analysis demonstrated a BCL-6 corepressor mutation, and methylation profiling matched with posterior fossa ependymomas A. He received craniospinal irradiation and focal boost with Vorinostat. Serial imaging after irradiation revealed a progressively decreasing tumor burden with nearly complete resolution of disease at 15 months. Histone deacetylase inhibitors demonstrate promise in treatment of carefully selected cases of ependymoma.